2005 IEEE Engineering in Medicine and Biology 27th Annual Conference 2005
DOI: 10.1109/iembs.2005.1615381
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality in brain intervention: models and applications

Abstract: Human body models are key components of VR surgical simulators. We overview here our efforts and share experience in constructing cerebral models and using them in VR-based applications for brain intervention. We have constructed four groups of brain atlases: anatomical, functional, vascular, and physically-based. The atlas-assisted VR systems discussed here are applied to stereotactic and functional neurosurgery, interventional neuroradiology, and brain stereotaxy. We also briefly feature our concept of futur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 19 publications
0
12
0
1
Order By: Relevance
“…Even with the beautiful three-dimensional images that can now be generated, the working views on the road map remain two-dimensional with only preprocessed images helping to predict where a coil will lie in complex anatomy or suggesting the anatomic relationship of an implanted device such as a stent (76). Virtual reality software is being designed in which a patient's vascular imaging data set can be manipulated and the treatment strategies "war-gamed" for the best solution; these systems also provide fertile ground for training new endovascular surgeons (111,155). Real-time MRI, which has been used experimentally, offers the promise of being able to treat patients with the aid of real-time three-dimensional imaging (145).…”
Section: The Endovascular Suitementioning
confidence: 99%
“…Even with the beautiful three-dimensional images that can now be generated, the working views on the road map remain two-dimensional with only preprocessed images helping to predict where a coil will lie in complex anatomy or suggesting the anatomic relationship of an implanted device such as a stent (76). Virtual reality software is being designed in which a patient's vascular imaging data set can be manipulated and the treatment strategies "war-gamed" for the best solution; these systems also provide fertile ground for training new endovascular surgeons (111,155). Real-time MRI, which has been used experimentally, offers the promise of being able to treat patients with the aid of real-time three-dimensional imaging (145).…”
Section: The Endovascular Suitementioning
confidence: 99%
“…Inexpensive commercially available hardware can be setup at home [1,2], while corporations are using VR to design mechanical systems and train pilots [3,4]. However, limited application is seen in the medical field.Most medical VR simulation focus on medical training, by incorporating anatomical models, physics models, haptics, and visualization to recreate surgical procedures [4][5][6]. These simulations teach foundational technical skills and show value for preoperative planning and image-guided surgery [4,7].…”
mentioning
confidence: 99%
“…Simulations provide opportunities to develop surgical plans [7], and practice teamwork skills [8]. Studies have shown that expenses of implementing VR technology can be offset by reduced operating room time [5] and s can shape the operating room of the future [6].Procedural planning using VR shows positive results for patient outcomes. One study looking at VR use for procedural planning found an increase in operational success, a decrease in 30-day mortality and an estimated cost savings by incorporating 3D imaging [9].…”
mentioning
confidence: 99%
See 2 more Smart Citations